Contingent Liabilities from Banks : How to Track Them? - Arslanalp, Serkan (IMF Working Papers; Working Paper ;, 2015)
In this paper, we develop a methodology to assess potential losses to the government that could arise from bank failures. The approach is intended to be simple, parsimonious, and used in real time. It generates an index that we call the banking sector contingent liability index (BCLI), based on the banking sector's size, concentration, diversification, leverage, and riskiness of assets. The index is illustrated for 32 advanced and emerging market economies from 2006 to 2013, as well as a group of banks including global systemically important banks (G-SIBs).